Racial and Ethnic Disparities in Community-Based Pharmacies: A Scoping Review - Tamera D. Hughes; Jessica S. Roller; Faustina Hahn; Stefanie P. Ferreri (MDPI AG, 2023)
As pharmacy practice shifts its focus toward population health care needs that serve public health, there is a need to understand community-based pharmacies' contributions to the reduction in health disparities. A scoping review was conducted to identify what community-based pharmacies in the United States are doing to target racial and ethnic disparities in community-based pharmacies. Forty-two articles revealed that community-based pharmacy services addressed racial and ethnic inequities in a variety of ways, including the types of interventions employed, as well as the ethnicities and conditions of the sample populations. Future work should focus on ensuring interventions are carried out throughout pharmacy practice and accessible to all racial and ethnic minoritized populations.